Pengenalan Lapangan Persekolahan pada Mahasiswa di SMA Negeri 9 Pekanbaru - Surya Ramadhan; Wirna Wiranti; Willyansah Willyansah (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to provide a better understanding of the school field for students at SMA Negeri 9 Pekanbaru. This activity is expected to broaden horizons and enhance the knowledge and competencies of students in the field of education. Through observation and interviews with teachers, students can learn about various aspects of learning and educational management that take place in schools. The methods used in this research include the collection of notes and documentation, where students reorganize and explain what they have learned. One of the observation activities conducted was an interview with the teacher regarding daily activities at the school, from student arrival to dismissal time. This activity aims to provide students with direct experience in understanding the educational process at school. In addition, this research also provides benefits to educational institutions as a reference for improving the quality of education, facilities and infrastructure, as well as learning activities. Thus, it is hoped that the results of this research can contribute to the development of better education in the future. Overall, this research is not only beneficial for students in enhancing their competencies but also for educational institutions in their efforts to improve and develop the existing education system.